Dielectric Strength Improvement of Natural Ester Insulation Oil via Mixed Antioxidants: Taguchi Approach - Sharin Ab Ghani; Zulkarnain Ahmad Noorden; Nor Asiah Muhamad; Hidayat Zainuddin; Muhammad Ilman Hakimi Chua Abdullah; Imran Sutan Chairul (Institute of Advanced Engineering and Science, 2017)
Recently, natural ester insulation (NEI) oils are found to be the best candidates to replace mineral-based insulation oils for oil-immersed transformer applications. However, NEI oils are prone to oxidation due to their poor oxidative stability which can be improved by adding antioxidants into the oils. Latest studies have also shown that the use of selected antioxidants improves the AC breakdown voltage (BdV) of NEI oils. However, the experiments in previous studies were designed using the conventional one-factor-at-a-time (OFAT) method, which requires a large number of samples to be tested in order to determine the optimum response. Thus, a Taguchi-based designed experiment is introduced in this study in replacement of the OFAT method. It is found that this method is capable of determining the optimum concentrations of propyl gallate (PG) and citric acid (CA) which will maximize the AC BdV and improve the oxidative stability of the NEI oil. An AC breakdown voltage test is conducted in accordance with the ASTM D1816 standard using Megger OTS60PB portable oil tester, in which the electrode gap distance is kept fixed at 1 mm. The results indicate that the addition of PG and CA antioxidants increases the AC BdV of the rapeseed-based NEI oil. It is found that the optimum concentrations of PG and CA antioxidant is 0.05 and 0.25 wt.%, respectively. Lastly, the model developed in this study is analysed using analysis of variance (ANOVA). Validation test is also conducted on the optimized NEI oil to determine its dielectric strength and oxidative stability.